Threats Hidden in Office Network: Mechanism of Credential Harvesting for Lateral Movement - Tung-Lin Lee (Atlantis Press, 2021)
With the advent of the Internet of Things (IoT) era, the concept of smart office has gradually come true. To facilitate the management, IoT devices often follow authentication mechanisms as windows domain used, which would cause severe problems once hackers steal those credentials. This study analyzes the restriction of previous research and proposes a new technique that could cause credential leaks and organizes an attack mechanism to evaluate the most suitable strategy in various scenarios.